Role of the medial olivocochlear efferent auditory system in speech perception in noise: a systematic review and meta-analyses. - Gafoor, Shezeen Abdul; Uppunda, Ajith Kumar (International Journal of Audiology, 2024)
The study investigated the relationship between the strength of the medial olivocochlear reflex (measured via contralateral inhibition of otoacoustic emissions) and speech perception in noise (obtained from behavioural identification task) through meta-analyses. A systematic review and random-effects meta-analysis of studies investigating the relationship in neurotypical adults was performed. The systematic search (in PubMed, Scopus, Science Direct and Google Scholar databases) revealed 21 eligible studies, which were critically appraised using the NIH tool for Observational Cohort and Cross-Sectional Studies. Meta-analysis was performed on 17 studies (374 participants) with fair to good quality. The results revealed that the medial olivocochlear reflex accounts for less than 1% of the variations in speech perception in noise in neurotypical individuals. Sub-group analyses conducted to address a few methodological differences also revealed no discernible association between the two variables. The results reveal no modulatory effect of the medial olivocochlear reflex assessed using contralateral inhibition of otoacoustic emission on the ability to perceive speech in noise. However, more data utilising alternative measures of medial olivocochlear reflex strength is necessary before drawing any conclusions about the role of the medial olivocochlear bundle in speech perception in noise.